Ferdinand Saussure's Semiotic Analysis of the Politicization of Social Assistance in the Film Dirty Vote - Marzuki, Nur Rofifah; Sonni, Alem Febri; Arianto, Arianto (LEGAL BRIEF, 2025)
This study analyzes the politicization of social assistance in the film Dirty Vote using Ferdinand de Saussure's semiotic approach. The concept of signifier and signified is used to identify and interpret the visual and verbal signs presented in the film. The results of the analysis show that elements such as party symbols, dominant colors, budget graphs, and narrative scenes illustrate the close relationship between the distribution of social assistance and certain political agendas. Signifiers such as the overlay text "politicization of social assistance" and images of officials in the campaign reflect a systematic pattern that utilizes social assistance for electoral interests. The resulting signifiers reveal criticism of the abuse of power, the inequality of aid distribution, and its impact on public trust in the government. By understanding the sign system used, this study highlights the importance of public awareness of the issue of the politicization of social assistance in the context of democracy seen from the perspective of communication semiotics studies